ANALISIS KINERJA KEUANGAN DENGAN MENGGUNAKAN RASIO PROFITABILITAS DAN RASIO LIKUIDITAS STUDI KASUS PADA USAHA JASA FOTOCOPY DI KOTA SORONG - Ferdinando Solissa (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2019)
This study aims to assess the company's financial performance in thePhotocopy Service business in the city of Sorong by using financial ratio analysisduring the period 2016-2018 in the company's financial statements.The research was conducted at a photocopy service business registered atthe Department of Trade and Industry in Sorong City. The method of datacollection carried out in this study is the documentary method through financialstatements. The sampling technique used is the saturated sample method. Themanager as the participating analysis unit is 10 photocopy service businessmanagers. Data analysis uses liquidity ratios and profitability ratiosThe results showed that the liquidity ratio in the business of photocopyingthe city of Sorong from 2016 to 2018 was good from current ratio, fast ratio, cashratio and net working capital ratio to total assets so that it could meet its shortterm liabilities in 2016 and 2018 it is good for operating profit margins and ROIeven though the net profit margin is still not optimal in 2018 as well as in 2016 sothere is a need for this business capability to increase profits.